Needs Analysis of Project Based Teaching Module Development in the Independent Curriculum - Mustadi, Ali; Wibowo, Setiawan Edi; Zubaidah, Enny; Supartinah, Supartinah; Sugiarsih, Septia; Sayekti, Octavian Muning (Jurnal Prima Edukasia, 2024)
This study aims to describe the needs analysis of developing a Project Based Teaching Module to increase the creativity of PGSD S1 students in designing independent curriculum-oriented elementary school learning. This study employed a mixed method approach, specifically utilizing a sequential explanatory design combination research design. The study employed quantitative methodologies and focused on 4th semester students in the PGSD FIPP UNY Study Program, resulting in a population size of 215 students. The study employed a random sampling technique to choose a group of students in their 4th semester. The sample technique employed the Isaac and Michael Tables. The collection of quantitative data was conducted using survey methodologies. The research instrument employed questionnaires that had been previously delineated with a grid. Additionally, the questionnaire instrument that was created to assess student creativity underwent validation and reliability testing prior to its use in the field. The gathered quantitative data were evaluated using descriptive methods. The quantitative data analysis was conducted using the Statistical Package for Social Science (SPSS) software, specifically version 25. Qualitative data were acquired by the utilization of qualitative methodologies, specifically through the means of interviews, observations, and documentation approaches. The tools employed in qualitative research encompass interview protocols, observation protocols, and documentation protocols. Meanwhile, qualitative data in this study was analyzed using data analysis (Miles &; Huberman, 2014) which includes condensation data, display data, and conclusion drawing / verification. The result of this research is that PGSD FIPP UNY students need teaching materials to support learning, especially in the Elementary School Indonesian Language and Literature Education Development Course. This is evidenced by the results of questionnaires filled out by 62 respondents from different classes, showing that the need for teaching materials for the Education Development course is needed by them. It is proven by the results of the questionnaire that 100% of students stated that they needed teaching materials for tool development, especially those based on the Merdeka Curriculum.